A Case of Unilateral Multicystic Dysplastic Kidney and Bilateral Vesicoureteral Reflux With Hyponatremia and Hyperkalemia: Multicystic Dysplastic Kidney and Vesicoureteral Reflux - Pourpashang, Paniz; Zahmatkesh, Arefeh; Mohkam, Masoumeh (Journal of Pediatric Nephrology, 2023)
Multicystic dysplastic kidney (MCDK) is defined as a variant of renal dysplastic with multiple non-communicating cysts separated by dysplastic parenchyma. Contralateral vesicoureteral reflux (VUR) is the most frequent coincidence genitourinary anomaly in children with unilateral MCDK. Here, we described a case of unilateral MCDK (right side) with bilateral third-grade VUR who first, underwent conservative therapy because of electrolyte disturbance and metabolic acidosis.